Arabic Language Learning Model Based on Sharf Serap Nalar Ibadah (SSNI): Increasing Understanding of Al-Qur’an - Maswani Maswani; Muhbib Abdul Wahab; Achmad Fudhaili (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to develop an Arabic language learning model based on the Sharf Serap Nalar Ibadah (SSNI) approach to improve the understanding of Quranic Arabic (BAQ) for learning citizens. This study also tested its validity, feasibility, and effectiveness. This research is a research and development (R&D) type with the ADDIE model. The research data source consisted of qualitative data in the form of interviews with experts in the field of Arabic learning materials and design, 3 instructors, 18 learning residents, and 2 BAQ alumni, in addition to the results of the analysis of BAQ learning documents. The qualitative data were analyzed using the Spradley model. While quantitative data is in the form of questionnaires from experts, instructors, learning residents, and BAQ learning outcomes which are analyzed using a Likert scale and descriptive statistics. The research findings show that the Arabic language learning model is based on the approach Sharf Absorption of Worship Reason (SSNI) very valid, feasible to use, and effectively increases understanding of mufradât BAQ in various word forms (sharfî) and sentence structures (nahwi) in order to understand the meaning and translation of the verses of the Al-Quran and the Hadith of the Prophet SAW., understand the readings of daily prayers and prayers, so that they can be more solemn in worship, accompanied by learning fun with the average value of the experimental class reaching 82.2 and the control class value of 73.6 with a difference in the value of 8.4, and the accumulated value or practicality average of 84.92% (practical category).